SISTEM PENUNJANG KEPUTUSAN PEMILIHAN MENU MAKANAN SEHAT SESUAI ANGKA KECUKUPAN GIZI (AKG) DENGAN ANALYTIC HIERARCY PROCESS (AHP) - Yulmaini S.Kom., M.Cs; Deni Dwi N.S (Jurnal Informatika, 2012)
Decision making is an action taken to solve a problem which is based on considerations facts or information and some experience related to the problem. Lack of knowledge and understanding of the importance of the implementation of a healthy menu is still difficult determine composition of healthy food menu correspond to nutritional adequacy rate. So that most of people still ignore that fact which is a big potential of disease cause at our body.  Along with the development of technology and more complex inside the calculation needs balanced nutrition in a variety of food menu then it is necessary designed a system to provide an assessment of the healthy menu selections using the Analytic Hierarchy Process (AHP). This system can provide a decision in the selection process of a healthy food menu according to body condition based on height and weight, age, specific conditions and activities undertaken. Keywords: decision making, AHP, healthy food menu